ANALYSIS OF GENERATION Z'S INTEREST IN MAKING SHARIA INVESTMENTS : Using Financial Technology Platforms - Ishak, Safrizal; Arifin, Muhammad; Amri, Khairul; Ubaidillah, Jainul (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2026)
This study aims to analyze generation Z's interest in making sharia investments using financial technology platforms. This study used a quantitative approach with a survey method through the distribution of questionnaires to Generation Z respondents in Banda Aceh City. The data obtained were analyzed using statistical analysis techniques to test the influence of independent variables on sharia investment interest. The results showed that the above factors partially and simultaneously influenced Generation Z's interest in sharia investment using financial technology platforms. Ease of use and perceived benefits were the dominant variables influencing investment interest. This study is expected to contribute to the development of sharia economic literature and serve as a reference for related parties, especially in increasing sharia investment interest among the younger generation through the use of technology.